The adenovirus E1A protein overrides the requirement for cellular ras in initiating DNA synthesis. - Stacey, D W (1994)
The adenovirus E1A protein can induce cellular DNA synthesis in growth-arrested cells by interacting with the cellular protein p300 or pRb. In addition, serum- and growth factor-dependent cells require ras activity to initiate DNA synthesis and recently we have shown that Balb/c 3T3 cells can be blocked in either early or late G1 following microinjection of an anti-ras antibody. In this study, the E1A 243 amino acid protein is shown through microinjection not only to shorten the G0 to S phase interval but, what is more important, to override the inhibitory effects exerted by the anti-ras antibody in either early or late G1. Specifically, whether E1A is co-injected with anti-ras into quiescent cells or injected 18 h following a separate injection of anti-ras after serum stimulation, it efficiently induces cellular DNA synthesis in cells that would otherwise be blocked in G0/G1. Moreover, injection of a mutant form of E1A that can no longer associate with p300 is just as efficient as wild-type E1A in stimulating DNA synthesis in cells whose ras activity has been neutralized by anti-ras. The results presented here show that E1A is capable of overriding the requirement of cellular ras activity in promoting the entry of cells into S phase. Moreover, the results suggest the possibility that pRb and/or pRb-related proteins may function in a ras-dependent pathway that enables E1A to achieve this activity.